Which equation has the same solutions as 2x + x - 3 = 0?
(1) (2x - 1)(x + 3) = 0 (3) (2x - 3)(x + 1) = 0
(2) (2x + 1)(x – 3) = 0 (4) (2x + 3)(x - 1) = 0

Respuesta :

Answer:

1 and 4 has same pairs of solution.

Step-by-step explanation:

Solutions for the given equations are:

\begin{gathered}1. (x+6)(x - 6) = 0\\(x+6) = 0, (x-6) = 0\\x = -6, x = 6\\\\2. (x + 6)(x + 6) = 0\\(x+6) = 0, (x+6) = 0\\x = -6, x = -6\\\\3. (x - 6)(x - 6) = 0\\(x-6) = 0, (x-6) = 0\\x = 6, x = 6\\\\4. (2x + 12)(2x - 12) = 0\\(2x+12) = 0, (2x-12) = 0\\x = -6, x = 6\\\\5. (2x - 12)(x - 12) = 0\\(2x-12) = 0, (x-12) = 0\\x = 6, x = 12\\\\6. (x+12)(x - 12) = 0\\(x+12) = 0, (x-12) = 0\\x = -12, x = 12\\\\7. (x +12)(x-6) = 0\\(x+12) = 0, (x-6) = 0\\x = -12, x = 6\end{gathered}

1.(x+6)(x−6)=0

(x+6)=0,(x−6)=0

x=−6,x=6

2.(x+6)(x+6)=0

(x+6)=0,(x+6)=0

x=−6,x=−6

3.(x−6)(x−6)=0

(x−6)=0,(x−6)=0

x=6,x=6

4.(2x+12)(2x−12)=0

(2x+12)=0,(2x−12)=0

x=−6,x=6

5.(2x−12)(x−12)=0

(2x−12)=0,(x−12)=0

x=6,x=12

6.(x+12)(x−12)=0

(x+12)=0,(x−12)=0

x=−12,x=12

7.(x+12)(x−6)=0

(x+12)=0,(x−6)=0

x=−12,x=6

(x+6)(x - 6) = 0 and (2x + 12)(2x - 12) = 0 have same pair of solutions.

Step-by-step explanation:

there you go :)

ACCESS MORE